Hadith #3307 - Sahih al-Bukhari - al-Rabi' bin 'Amila الربيع بن عميلة (Sahih al-Bukhari)
`Uqba bin `Amr said to Hudhaifa, “Won’t you relate to us of what you have heard from Allah’s Apostle ?” He said, “I heard him saying, “When Al-Dajjal appears, he will have fire and water along with him. What the people will consider as cold water, will be fire that will burn (things). So, if anyone of you comes across this, he should fall in the thing which will appear to him as fire, for in reality, it will be fresh cold water.” Hudhaifa added, “I also heard him saying, ‘From
Grade: Sahih

Hadith #3333 - Sahih al-Bukhari - al-Rabi' bin 'Amila الربيع بن عميلة (Sahih al-Bukhari)
`Uqba said to Hudhaifa, “Won’t you narrate to us what you heard from Allah’s Messenger (ﷺ) ?” Hudhaifa said, “I heard him saying, ‘Death approached a man and when he had no hope of surviving, he said to his family, ‘When I die, gather for me much wood and build a fire (to burn me),. When the fire has eaten my flesh and reached my bones, take the bones and grind them and scatter the resulting powder in the sea on a hot (or windy) day.’ (That was done.) But Allah collected his pa
Grade: Sahih